Presentation is loading. Please wait.

Presentation is loading. Please wait.

KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3.

Similar presentations


Presentation on theme: "KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3."— Presentation transcript:

1 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3

2 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3

3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 Cu e → Cu +1

4 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 Cu e → Cu +1 2J e → J 0 2

5 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 Cu e → Cu +1 2J e → J

6 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 → Cu +1 J+J KNO 3 Cu e → Cu +1 2J e → J

7 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ -1 +Cu +2 (NO 3 ) 2 →2Cu +1 J+J 0 2 +KNO 3 Cu e → Cu +1 2J e → J

8 KJ + Cu(NO 3 ) 2 →2CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 →2CuJ + J 2 + KNO 3 KJ +2Cu(NO 3 ) 2 →2CuJ + J 2 + KNO 3 KJ +2Cu(NO 3 ) 2 →2CuJ + J 2 + KNO 3 KJ +2Cu(NO 3 ) 2 →2CuJ + J 2 +4KNO 3 KJ +2Cu(NO 3 ) 2 →2CuJ + J 2 +4KNO 3

9 4KJ+2Cu(NO 3 ) 2 →2CuJ + J 2 +4KNO 3 4KJ+2Cu(NO 3 ) 2 →2CuJ + J 2 +4KNO


Download ppt "KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3 KJ + Cu(NO 3 ) 2 → CuJ + J 2 + KNO 3."

Similar presentations


Ads by Google